How do we manage and treat a patient with multiple sclerosis at risk of tuberculosis?. (November 2014) - Fragoso, Yara Dadalti; Adoni, Tarso; Anacleto, Andrea; Brooks, Joseph Bruno Bidin; Carvalho, Margarete de Jesus; Claudino, Rinaldo; Damasceno, Alfredo; Ferreira, Maria Lucia Brito; Gama, Paulo Diniz da; Goncalves, Marcus Vinicus Magno; Grzesiuk, Anderson Kuntz; Matta, Andre Palma da Cunha; et al.
Abstract : Tuberculosis continues to be a serious health problem worldwide. The disease continues to be underdiagnosed and not properly treated. In conditions that affect the immune system, such as multiple sclerosis (MS), latent tuberculosis may thrive and reactivate during the use of immunomodulatory and immunosuppressive drugs. Among the best treatment options for patients with latent or active tuberculosis who have MS are IFN-β, glatiramer acetate and mitoxantrone. Drugs leading to a reduced number and/or function of lymphocytes should be avoided or used with caution. Tuberculosis must always be investigated in patients with MS and treated with rigor.